Evidence, reasons and randomness - Levanon, Liat (London [England] : Hart Publishing, 2022)
"Should statistical evidence be used as legal evidence? The book addresses this question by considering the relationship between evidence, randomness and justifying reasons. A distinction will be drawn between evidence that can justify critical judgements and evidence that can only justify non-critical judgements. Evidence can justify critical judgement only if it can support all the propositions of the judgement, thus leaving none of the propositions random. Evidence can justify non-critical judgements even where it leaves some propositions random. One implication is that 'naked statistical evidence' can only justify non-critical judgements. The proposed evidential distinction will be further explored and attuned in a range of legal and related extra-legal contexts. These will include the context of: - criminal and civil judgements; - allocation of burdens based on profiling (like in 'stop and search'); - distribution of resources based on profiling; - private judgements in everyday life; and - justified belief."--
Part I: Choosing Evidential Methods -- 1. Methods of Proof in the Law and Beyond -- 2. Critical and Non-critical Judgments -- 3. Random Propositions -- 4. Non-Randomness in Critical Judgment Part II: Legal Judgments -- 5. Legal Judgments: Standards, Attitudes, Contexts -- 6. Non-Randomness in Legal Judgements: Special Considerations Part III: Beyond Legal Judgments -- 7. Private Judgments -- 8. Profiling and the Allocation of Burdens -- 9. Profiling and Distribution of Resources -- 10. Knowledge and Justified Belief -- 11. Conclusions
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Evidence (Law) -- Statistical methods; Electronic books